Project pedagogy and the development of discursive skills - Jaimes Carvajal, Gladys (Rastros Rostros, 2023)
Project Pedagogy emerges as an alternative of school action aimed at recovering the meaning of educational processes as cultural practices involving actors, purposes, activities and contexts. The following principles can be considered
Keywords: Project; pedagogy; development; discursive; skills